Sistemas baseados em bentonitas com aminas cíclicas e amilorida - rotas de síntese e ensaios de emissão - Oliveira, Leandro Severino de (2016)
The bentonite term designates gross clays containing at least 50% of smectite and particularly montmorillonite. The smectite have features like lamellar structures, ion exchange capacity, variability of the chemical composition and the electrical charge of the lamellae, which determine the properties in interactions with organic and inorganic substances. Changes in physical and chemical properties of these materials after intercalation of organic compounds has drawn attention due to wide applicability by these hybrids. polar organic molecules such as amines, may replace the water molecules that occupy the interlayer space, resulting in organofílicos materials. Within this perspective, we obtained hybrid bentonite intercalation / amines using bentonite exchanged with sodium and calcium cations. In this case we have used two cyclic diamines of pharmacological importance, an aliphatic, piperazine (PPZ) and an aromatic, pyrazine (PRZ) for hybrid formation by several synthesis routes. Then the drug amiloride hydrochloride, which has in its structure the pyrazine ring is loaded in calcium bentonite sample for subsequent emissions testing. The characterization techniques such as, XRD, IR, TEM, inter alia, the efficiency in all cases. Thus, the results indicate a possible application of such hybrids for obtaining the metal complexes and the use of these systems for controlled emission tests in view of the PPZ have pharmacological properties while PRZ is a base molecule for various drugs, such as amiloride, for example.